Intestinal obstruction in a tertiary care centre in India: Are the differences with the western experience becoming less?. (December 2021) - Jena, Suvendu Sekhar; Obili, Ravi Chandra Reddy; Das, Sri Aurobindo Prasad; Ray, Samrat; Yadav, Amitabh; Mehta, Naimish N.; Nundy, Samiran
Abstract: Background: Patients with intestinal obstruction consist of a major proportion of emergency room visits and the complication is associated with a significant morbidity and mortality. It has a diverse aetiology which varies from country to country. In developed countries it is mainly due to adhesions and in developing countries due to obstructed hernias. Although there are numerous studies from the western world on this subject there have been few recent publications from the developing world. Patients and methods: We retrospectively analyzed all the patients admitted with intestinal obstruction to our department from January 1996 to December 2019. Their demographic data, duration of symptoms before presenting to the hospital and interval between admission and surgery were noted along with the cause and level of obstruction. The type of procedure, post-operative complications, mortality or whether re-exploration was done were also noted. Post-operative complications were graded according to the Clavien Dindo classification. Results: A total of 986 patients presented with intestinal obstruction during this period out of which 743 patients underwent surgery. The commonest cause of obstruction was adhesions in 273 (36.7%) – the proportion increased significantly from 23% in 1996–2004 to 51.6% in 2013–2019. This was followed by carcinoma [130(17.5%)], tuberculosis [111(14.9%)], strictures [94(12.7%)] and hernia (5.4%). Colorectal surgery was the most common previous procedure in the adhesions group [85(31.1%)].The overall operative mortality was 41 (5.5%). Conclusion: The aetiology of intestinal obstruction in our hospital is now mainly due to adhesions and is thus shifting towards the western pattern. But tuberculosis and obstructed inguinal hernias still constitute of a sizable proportion of our patients. Highlights: Post-operative adhesions have now become a common cause of intestinal obstruction our tertiary care centre situated in a developing country. These were most commonly preceded by operations on the colon and rectum. Our overall mortality rate was comparable with those reported from the west. Old age, malignancy and strangulation were associated with a higher risk of mortality as has been the experience from other centres. Compared to Western reports our patient population was younger, males predominated. Although the proportion of patients with adhesions is rising tuberculosis continues to be an important cause for intestinal obstruction.